The Stories of Heinrich von Kleist: A Critical Bilingual Edition : Volume 2: The Betrothal in St Domingo, The Beggarwoman of Locarno, The Foundling, St Cecilia or The Power of Music, The Duel. - Contag, Johannes (Amsterdamer Beiträge zur neueren Germanistik, 2026)
Heinrich von Kleist (1777-1811) is one of Germany's pre-eminent writers, and his works have remained as captivating and thought-provoking as ever. Although translated into English previously, this is the first scholarly, bilingual edition of Kleist's stories, wherein his dictional idiosyncrasies are rendered closely and systematically. Comprehension is aided by lexical, intertextual and translational annotations, and individual story commentaries offer historical context and interpretational starting points. This second of two volumes is based on Kleist's collection Erzählungen. Zweiter Theil (1811) and includes an introduction to Kleist's Anglophone reception and to the stories' previous translations, as well as a detailed appendix that outlines Contag's own translational processes.